Effect of cogongrass biochar enriched with nitrogen fertilizer dissolved in seaweed liquid extract on soil water content of Ultisol - Kilowasid, Laode Muhammad Harjoni; Alam, Syamsu; Rakian, Tresjia Corina; Ansar, Nurul Awalia; Nurfadillah; Ramdan, Nurfatihah Hijrah; Jaya, Irfan; Suryana; Agustin, Widia; Rahni, Nini Mila; Mashuni; Safuan, La Ode (Journal of Degraded and Mining Lands Management, 2024)
Ultisol dry land is characterized by significantly low organic carbon content, an important factor influencing soil water content and physico-chemical dynamics. The addition of N fertilizer dissolved in seaweed liquid extract as an enrichment solution can change the character of biochar. Therefore, this study aimed to analyze the characteristics of cogongrass biochar enriched with dissolved N fertilizer in seaweed extract of different species and assess its impact on soil water content in Ultisol. Urea was used as a nitrogen source, and biochar enriched with N fertilizer dissolved in seaweed liquid extract from Kappapychus alvarezii, Sargassum sp., and Ulva lactuca was tested. Biochar dose used was 20% of soil weight with a 10% extract concentration for each type. Furthermore, five-level treatments were tested in a pot experiment, namely (i) without biochar, (ii) biochar unenriched, (iii) enriched with N fertilizer dissolved in K. alvarezii extract, (iv) enriched with N fertilizer dissolved in Sargassum sp. extract, and (v) biochar enriched with N fertilizer dissolved in U. lactuca extract. Each treatment was repeated three times, following a randomized block design. The results showed that cogongrass biochar enriched with N fertilizer dissolved in seaweed extract had a more amorphous surface morphology structure. The proportion of elements and functional groups in cogongrass biochar changed. Enriched biochar increased Ultisol moisture levels, but water holding capacity and retention were lower than the unenriched sample.